Existence of Positive Solutions for a Nonlinear Higher-Order Multipoint Boundary Value Problem - Min Zhao; Yongping Sun (Abstract and Applied Analysis)
We study the existence of positive solutions for a nonlinear higher-order multipoint boundary value problem. By applying a monotone iterative method, some existence results of positive solutions are obtained. The main result is illustrated with an example.